Researching Informal Skills Learners: Considering Work Interruption and Vulnerabilities - Baral, Durga Prasad (Journal of Technical and Vocational Education and Training, 2023)
Informal skills learners are the workers who learn occupational skills during their work in an informal setting. Little research has been done on their learning environment and processes in a context similar to Nepal and many other developing countries. Such research deficit is more pronounced in informal skills learning research. In this paper, I address this gap. Based on two concepts - work interruptions and vulnerability of novice informal skills learners - I discuss methodological and ethical dilemmas while researching these people. Drawing from my PhD research carried out in four occupational sectors - pottery, metalcrafts, fast food and two-wheeler mechanics in Nepal (in Kathmandu valley), I first analyse the general features of informal skills learners’ vulnerability which might further increase while spending time with the researchers. The ethical dilemmas researchers might face while researching vulnerable skills learners are about minimizing work interruption and avoiding harm to them. At the end, I propose specific ways of dealing with informal skills learners while conducting fieldwork. The study expects to increase the researchers’ awareness while dealing with vulnerable workers and learners, and provides a track for further research in the area.